2012
DOI: 10.1089/jwh.2011.2845
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum Use of Long-Acting Reversible Contraception in a Military Treatment Facility

Abstract: In our institution, LARC is highly desired and utilized within 12 weeks postpartum with African-American ethnicity and age <25 years predictive of use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…The relationship between the wealth status indicator and PPFP utilization to a greater extent is related to both financial autonomy and access to resources necessary to purchase the required health inputs [7, 26]. Further in Rwanda, an equity analysis of performance based financing in Rwanda, showed increased utilization of services at health facilities across wealth status [20, 27, 28, 29]. Among the few studies conducted in both countries, one showed wealth status as a significant factor in influencing pregnancy history and current use of contraception in Rwanda and Burundi [30].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between the wealth status indicator and PPFP utilization to a greater extent is related to both financial autonomy and access to resources necessary to purchase the required health inputs [7, 26]. Further in Rwanda, an equity analysis of performance based financing in Rwanda, showed increased utilization of services at health facilities across wealth status [20, 27, 28, 29]. Among the few studies conducted in both countries, one showed wealth status as a significant factor in influencing pregnancy history and current use of contraception in Rwanda and Burundi [30].…”
Section: Discussionmentioning
confidence: 99%
“…This implies that PPFP was higher among the younger women compared to the older women. In a study on use of long active reversible contraceptives at a military facility in the US, the study revealed that younger women <25 years were more likely to use these methods [ 33 ]. Similar results were also reported concerning current contraceptive use in Malawi, where younger women were more likely to use contraceptives compared to older women [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…This prospective study is important because it is one of the few published studies to describe patterns of contraceptive uptake and discontinuation among postpartum women with 1 year of follow-up in sub-Saharan Africa. Other studies among postpartum women have only been able to assess contraceptive uptake at hospital discharge or within the first 3 months postpartum [ 24 , 25 ]. We were able to describe baseline characteristics of women who used LARC over 1 year and the timing of use and discontinuation.…”
Section: Discussionmentioning
confidence: 99%